Maternal and perinatal outcomes following peripartum hysterectomy from a single tertiary centre. (19th October 2013) - Jones, Bryony; Zhang, Eko; Alzouebi, Aisha; Robbins, Tanya; Paterson‐Brown, Sara; Prior, Tomas; Kumar, Sailesh
<x xml:space="preserve">Abstract</x> Background We investigated the indications for and maternal and perinatal outcomes following peripartum hysterectomy in a single large tertiary centre. Materials and methods All cases of peripartum hysterectomy between 2000 and 2011 were investigated. Data regarding maternal demographics, previous obstetric and gynaecological history, indications for hysterectomy, and details of haemorrhage, surgical complications and neonatal outcomes were collected. Results There were 47 cases of peripartum hysterectomy of 55 262 births giving an incidence of 0.85 per 1000 births. Forty‐one cases were total hysterectomies, while six were subtotal procedures. A total of 70.2% of cases were performed because of a morbidly adherent placenta, 27.7% for uterine atony and 2.1% for uterine rupture. The median estimated blood loss was 7290 mL. The overall surgical complication rate was 44.6% with bladder injury (19.1%) and sepsis (12.8%) commonest. Intensive care admission was required in 57.4% of women. Conclusions Peripartum hysterectomy is a major procedure carrying a high morbidity rate. In this series, maternal survival was 100%.